Challenges in the diagnosis of hemophagocytic lymphohistiocytosis: Recommendations from the North American Consortium for Histiocytosis (NACHO). Issue 11 (24th July 2019) - Jordan, Michael B.; Allen, Carl E.; Greenberg, Jay; Henry, Michael; Hermiston, Michelle L.; Kumar, Ashish; Hines, Melissa; Eckstein, Olive; Ladisch, Stephan; Nichols, Kim E.; Rodriguez‐Galindo, Carlos; Wistinghausen, Birte; et al.
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a syndrome of pathologic immune activation, often associated with genetic defects of lymphocyte cytotoxicity. Though a distinctive constellation of features has been described for HLH, diagnosis remains challenging as patients have diverse presentations associated with a variety of triggers. We propose two concepts to clarify how HLH is diagnosed and treated: within the broader syndrome of HLH, "HLH disease" should be distinguished from "HLH disease mimics" and HLH subtypes should be categorized by specific etiologic associations, not the ambiguous dichotomy of "primary" and "secondary." We provide expert‐based advice regarding the diagnosis and initiation of treatment for patients with HLH, rooted in improved understanding of its pathophysiology.